The Altar and the Rail: “Catholicity” and African American Inclusion in the 19th Century Episcopal Church - Jennifer Snow (Religions, 2021)
Examining the denominational history of The Episcopal Church from the point of view of mission shifts the view of the church’s nature and its most important figures. These become those people who struggled to overcome boundaries of race, culture, and geography in extending the church’s reach and incorporating new people into it, and puts issues of racial relationships at the forefront of the church’s story, rather than as an aside. White Episcopalians from the 1830s forward were focused heavily on the meaning of “catholicity” in terms of liturgical and sacramental practice, clerical privilege, and the centrality of the figure of the Bishop to the validity of the church, in increasingly tense and conflicted debates that have been traced by multiple scholars. However, the development of catholicity as a strategic marker of missional thinking, particularly in the context of a racially diverse church, has not been examined. The paper investigates the ways in which Black Episcopalians and their white allies used the theological ideal of catholicity creatively and strategically in the nineteenth century, both responding to a particular missional history and contending that missional success depended upon true catholicity.